Kontribusi Destinasi Wisata dalam Mengoptimalkan Retribusi Dinas Pariwisata Kota Bukittinggi - Nursya’diah Nursya’diah; Rini Elvira; Iiz Izmuddin; Zuwardi Zuwardi (Lembaga Pengembangan Kinerja Dosen, 2026)
The background of this research is the tendency for retribution realization from tourist destinations in Bukittinggi City to be consistently below its target. The study aims to measure the contribution of tourist destinations in optimizing the retribution of the Bukittinggi City Tourism Office. The research uses a descriptive quantitative method, collecting secondary data from the Bukittinggi City Tourism Office (2015-2024) and primary data (interviews and observations). The research objects include the Kinantan Wildlife and Cultural Park (TMSBK) and the Japanese Cave Panorama Park (TPLJ). The results show that the contribution of tourist destinations to retribution is quite significant, with the highest percentage reaching 49.39% in 2024 and an average of 50.51% in the